New Paleomagnetic Constraints on the Early Cretaceous Paleolatitude of the Lhasa Terrane (Tibet) - Li, Zhenyu; Ding, Lin; Laskowski, Andrew K.; Burke, William B.; Chen, Yaofei; Song, Peiping; Yue, Yahui; Xie, Jing (Frontiers in Earth Science, 2022)
New zircon U-Pb dating results from the Zonggei Formation volcanics indicate that the volcanic rocks formed at ~114-110 Ma. Paleomagnetic data, petrography, and rock magnetism confirm the primary nature of isolated characteristic remanent magnetizations carried by titanomagnetite and hematite. Statistical analysis of the combined results from the Zonggei and Duoni formations reveals a group-mean direction of D±ΔD=0.4°±6.0°, I±ΔI=22.2°±5.6°, α95=5.6°, k=35.2 after bedding correction based on 20 group-mean directions. The corresponding paleopole was calculated to be λp=70.3°N, φp=270.5°E with A95=5.2°. Interpretation of our data alongside Cenozoic data from the Tethyan-Himalaya indicates that the India-Asia collision initiated by 61.7±3.0 Ma at 13.0°±1.8°N assuming a single-collision model. Intracontinental crustal shortening totals 1770±470 km took place on the Asian side since the onset of India-Asia collision. Furthermore, the data show that the Neo-Tethys Ocean reached its maximum N-S width of 7100±530 km at ~132 Ma and shrank to 6400±550 km by ~115±5 Ma. This is consistent with previous estimates based on geophysical images of the subducted Neo-Tethyan slab beneath Eurasia.